THE EFFECTIVENESS OF LEARNING ENGLISH VOCABULARY USING THE MODELLING THE WAY METHOD - Herliani, Herliani; Suhendi, Andang (JOURNAL OF LANGUAGE, 2024)
This qualitative study investigates the effectiveness of the modeling the way (MTW) method in enhancing the learning of English vocabulary among third-year students at MTS Ta'dib Al-Mu'allimin Al-Islamy. The MTW method, which emphasizes the role of modeling and imitation in language learning, was implemented in a controlled classroom setting to assess its impact on students' vocabulary acquisition. The data were collected through observations, interviews, and a vocabulary test administered before and after the intervention. The findings indicate that the MTW method significantly improved students' vocabulary retention and recall, with a notable increase in their ability to use new words in context. Furthermore, the study highlights the importance of teacher modeling and student engagement in the learning process. Then, this study suggests that the MTW method can be a valuable tool for English language instructors seeking to enhance their students' vocabulary skills. The study's implications for language teaching and learning are discussed for emphasizing the potential of the MTW method to improve students' language proficiency and overall academic performance.